EKSISTENSI DONGENG SIRAH NABAWIYAH SEBAGAI STIMULASI PENDIDIKAN KARAKTER RELIGIUS ANAK USIA DINI - Ervina; Saudah (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This service to society is motivated by developments in the times that continue to develop from time to time. Based on this, it is necessary to provide stimulation in terms of strengthening so that children have religious character education through the Sirah Nabawiyah fairy tale. The aim of this community service is so that children can get to know the Prophet Muhammad SAW and emulate the stories that have been told to children. Apart from that, so that children have good character education based on the qualities of the Prophet Muhammad SAW. The targets for community service participants are children aged 5-6 years in the Palangka Raya City area, Central Kalimantan, Indonesia and students of the Early Childhood Islamic Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Palangka Raya, who are also actively involved in the activities. the. The results of this community service show that children are very enthusiastic in following the fairy tales that are told and enthusiastic. Activities carried out with direct practice include reading the Sirah Nabawiyah fairy tale directly to children to make it easier for children to understand the fairy tale. The hope is that through the Sirah Nabawiyah fairy tale for early childhood, it will be able to stimulate children's religious character education, so that the goal of stimulation will be achieved optimally.